Association of Dorsal Subcutaneous Fat Thickness, Paraspinal Muscle Fat Infiltration, Modic Changes, and Demographic Factors with Lumbar Disc Degeneration on Magnetic Resonance Imaging - Audrina Ernes; Inda Kania M; Nyi Raden Siti Vissy Puspa Dewi Muharam (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Lumbar disc degeneration is a common contributor to chronic low back pain. Magnetic resonance imaging enables assessment of disc degeneration and related factors, including dorsal subcutaneous fat thickness, paraspinal muscle fat infiltration, Modic changes, age, and sex. Methods: This quantitative cross-sectional study used consecutive sampling of patients who underwent non-contrast lumbar MRI at Royal Prima General Hospital, Medan, from September to November 2025. A total of 253 samples were analyzed. Lumbar disc degeneration was graded using the modified Pfirrmann system, paraspinal fat infiltration using the Goutallier classification, and Modic changes using standard MRI criteria. Statistical analysis was performed using SPSS. Result: Lumbar disc degeneration tended to be more severe in the lower lumbar levels, particularly L4-L5 and L5-S1. Paraspinal muscle fat infiltration, Modic changes, and age showed significant associations with lumbar disc degeneration. Dorsal subcutaneous fat thickness and sex did not show significant associations with degeneration across the analyzed levels. Conclusions: Paraspinal muscle fat infiltration, Modic changes, and age were significantly associated with lumbar disc degeneration on MRI, whereas dorsal subcutaneous fat thickness and sex were not. These findings support careful MRI evaluation of paraspinal muscle quality and endplate changes in patients with lumbar degeneration.